2012
DOI: 10.1093/infdis/jis753
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Immunogenicity, and Surrogate Markers of Clinical Efficacy for Modified Vaccinia Ankara as a Smallpox Vaccine in HIV-Infected Subjects

Abstract: MVA is a promising candidate as a safer smallpox vaccine, even for immunocompromised individuals, a group for whom current smallpox vaccines have an unacceptable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 31 publications
(32 reference statements)
3
77
0
5
Order By: Relevance
“…Although total antibody titers were significantly higher in healthy compared with HIV-infected vaccinia-naive subjects, PRNT GMT values were similar at the 26 week follow-up visit. This result is consistent with the results of a smaller study [16], although the trial reported here included subjects with more advanced disease (CD4 count as low as 200 cells/µL compared with >350 cells/µL). Although a suppressed immune response in HIV-infected subjects is generally expected and frequently observed with other vaccines [21], total antibody titers in HIV-infected subjects were still high and comparable to titers in healthy subjects given first- and second-generation live smallpox vaccines [14, 16], justifying the conclusion that immune responses correlating to protection had been induced in this immunocompromised population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although total antibody titers were significantly higher in healthy compared with HIV-infected vaccinia-naive subjects, PRNT GMT values were similar at the 26 week follow-up visit. This result is consistent with the results of a smaller study [16], although the trial reported here included subjects with more advanced disease (CD4 count as low as 200 cells/µL compared with >350 cells/µL). Although a suppressed immune response in HIV-infected subjects is generally expected and frequently observed with other vaccines [21], total antibody titers in HIV-infected subjects were still high and comparable to titers in healthy subjects given first- and second-generation live smallpox vaccines [14, 16], justifying the conclusion that immune responses correlating to protection had been induced in this immunocompromised population.…”
Section: Discussionsupporting
confidence: 92%
“…Modified vaccinia Ankara was also shown to induce immune responses comparable with conventional VACV-based vaccines [14, 15]. Populations at an increased risk to receive first- and second-generation smallpox vaccines (ie, subjects with HIV-infection [16], atopic dermatitis [17], or immune-suppressive therapy [18], respectively) tolerated vaccination with MVA well and had a good immune response. To further evaluate MVA as a smallpox vaccine in at-risk individuals, this Phase II trial was conducted to compare the safety and immunogenicity of MVA in HIV-infected individuals and healthy controls.…”
mentioning
confidence: 99%
“…BN (primary assays) used vaccinia-Western Reserve (replicating vaccinia) [7] and BN-MVA (non-replicating vaccinia in humans) in the plaque reduction neutralizing antibody (PRNT 50 ) assay [8] and ELISA [8], respectively. Saint Louis University (SLU) (secondary assays) used ATCC MVA (VR-1508) as the assay antigens in the ELISA [30] and PRNT 60 [31] assay.…”
Section: Immunogenicity Assaysmentioning
confidence: 99%
“…IMVAMUNE® is a modified vaccinia Ankara (MVA)-based smallpox vaccine, derived from MVA-597. IMVAMUNE ® is replicationrestricted to avian cells [4,5] and has an improved safety profile [6][7][8][9]; however, its efficacy against variola has not been tested. Both liquid and lyophilized formulations of IMVAMUNE® were tested in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Various immunization studies using highly attenuated MVA in non-human primates or in clinical trials have demonstrated promising results that MVA is safe, well tolerated, and immunogenic (Earl et al, 2004;Frey et al, 2014;Greenberg et al, 2013;Hatch et al, 2013;Walsh et al, 2013;Wilck et al, 2010). Highly attenuated vaccinia, such as MVA, was shown to minimize primary cutaneous lesions induced by a challenge with replication-competent vaccinia and to reduce viral shedding, indicating that replication-incompetent vaccinia strains could serve as a primer to modulate the immune response and allow subsequent immunization with a standard vaccinia vaccine (see the review by Walsh and Dolin [2011]).…”
Section: Discussionmentioning
confidence: 99%